Time Provisions in Standard Forms of Local and International Construction Contract - Zhe Huei, Ling; Sim Nee, Ting (UNIMAS Publisher, 2010)
This paper is to present an analysis on the time related clauses and provisions in the current local (used in Malaysia) and international construction contracts.